Analysis of 2D Beam Structure Using the Matrix Method Using the PTC Mathcad and SAP2000 Applications - Yazid, Muhammad; Doni Rinaldi Basri; Ahmad Kurnain; Muhammad Defri Wahyudi (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2024)
Concrete beam structure that functions as an element to support bending loads and shear forces. The PTC Mathcad application software has a built-in matrix method, which makes it very easy to use to create simple structural analysis programs using the stiffness matrix method. The aim of this research is to create a simple analysis program using the PTC Mathcad application to analyze 2D beam structures using the matrix method and compare the analysis results with the SAP2000 application. PTC Mathcad and SAP2000 analysis will produce joint reaction values ​​for force, moment, and joint displacement for each beam model. Based on the results of the comparative analysis of internal force results produced from the PTC Mathcad application and the SAP2000 application, it was found that the